Frailty Is Associated With Decreased Time Spent at Home After Critical Illness: A Population-Based Study. (August 2021) - Hendin, Ariel; Tanuseputro, Peter; McIsaac, Daniel I.; Hsu, Amy T.; Smith, Glenys A.; Begum, Jahanara; Thompson, Laura Hilary; Stelfox, Henry T.; Reardon, Peter; Herritt, Brent; Chaudhuri, Dipayan; Rosenberg, Erin; et al.
Background: Frailty is characterized by vulnerability to stressors due to an accumulation of multiple functional deficits. Frailty is increasingly recognized as a risk factor for accelerated functional decline, increasing dependency, and risk of mortality. The objective of this study was to examine the association of frailty, at the time of critical care admission, with days alive at home and health care costs post-discharge. Methods: This retrospective cohort study used linked administrative data (2010-2016) in Ontario, Canada. We identified all patients admitted at the intensive care unit (ICU), aged 19 years and above, assessed using the Resident Assessment Instrument for Home Care (RAI-HC), within 6 months prior to index hospitalization including an ICU stay. Patients were stratified as robust, pre-frail, or frail based on a validated Frailty Index. The primary outcome was days alive at home in the year after admission. Secondary outcomes included mortality, health care–associated costs, ICU interventions, long-term care admissions, and hospital readmissions. Results: Frail patients spent significantly fewer days at home within 1 year of index hospitalization (mean 159 days vs 223 days in robust cohort, P < .001). Mortality was higher among frail patients at 1 year (59.6% in the frail cohort vs 45.9% in robust patients; odds ratio for death 1.59 [1.49-1.69]). Frail patients also had higher rates of long-term care admission within 1 year (30.1% vs 10.6% in robust patients). Total health care–associated costs per person alive were $30 450 higher the year after admission in the frail cohort. Conclusions: Frailty prior to ICU admission among patients who were eligible for RAI-HC assessment was associated with higher mortality and fewer days spent at home following admission. Frail patients had markedly higher rates of long-term care admission and increased costs per life saved following critical illness. These findings add to the discussion of risk–benefit trade-offs for ICU admission.